OPTIMIZATION OF OUKUP STEAM BATHS AS ECO-WELLNESS TOURISM ATTRACTIONS : OPTIMIZATION OF OUKUP STEAM BATHS AS ECO-WELLNESS TOURISM ATTRACTIONS - Batubara, Rima Pratiwi; Setiawan, Aditya Sugih (Jurnal Sosial Humaniora, 2023)
Karo Regency is one of the regencies in North Sumatra, Indonesia. Oukup is a traditional Karo steam bath using spices. Oukup is usually used as a cultural activity, but currently it tends to be used as a front for prostitution businesses. This research was conducted to describe the potential possessed by oukup as a traditional Karo steam bath which is then expected to become an option for the development of health ecotourism in Indonesia. This research is a descriptive research with an exploratory survey approach with a phenomenology approach. Data analysis was carried out by analyzing supply as an object of supply by looking at the indicators of health tourism resources. Optimization of oukup as an attraction for health ecotourism is by establishing an oukup observer organization, making policies and regulations related to oukup development, development of oukup objects, cultivating medicinal plants as materials for the implementation of oukup and those related to oukup as well as development of marketing and promotion of oukup products.